On ascending and subnormal subgroups of infinite factorized groups - De, Glovanni F.; Sysak, Ya. P.; Franclosi, S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider an almost hyper-Abellan group G of a finite Abelian sectional rank that is the product of two subgroups A and B. We prove that every subgroup H that belongs to the intersection A ∩ B and is ascending both in A and B is also an ascending subgroup in the group G. We also show that, in the general case, this statement is not true.